Kajian Filosofis Tradisi Aci Keburan Di Pura Hyang Api Desa Adat Kelusa Kecamatan Payangan Kabupaten Gianyar - Putu Sukariawan; Nyoman Suardika; Ida Bagus Eka Suadnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Religious tradition is basically a religious institution that has been considered standard by its supporting community. One of the unique traditions in Payangan District, Gianyar Regency is the tradition of aci burial. Aci keburan is a tradition that must be carried out because of the belief that if it is not carried out then the community will be attacked by disease outbreaks (grubug). There is a value contained in the aci keburan tradition in the Kelusa customary village community, which is different from tabuh rah because the aci keburan tradition emphasizes more on religious values and religious values. social. This research will explore the tradition of aci keburan at Hyang Api Temple, Kelusa Village, Payangan District, Gianyar Regency. The issues examined in this study are (1) Why is the Aci Keburan Tradition carried out at the Hyang Api Temple, Kelusa Traditional Village, Payangan District, Gianyar Regency? (2) How is the implementation of the Aci Keburan Tradition at Hyang Api Temple, Kelusa Traditional Village, Payangan District, Gianyar Regency? And (3) What is the philosophical meaning of the Aci Keburan tradition at Hyang Api Temple, Kelusa Traditional Village, Payangan District, Gianyar Regency. This study analyzed two basic theoretical foundations that correlated with each other, namely the theory of religion and the theory of value. Data collection was carried out using observation techniques, interviews, and document studies using the research methodology that had been designed. Data were analyzed and processed descriptively through three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the basis for carrying out the aci burial tradition at Hyang Api Temple in Kelusa Traditional Village are (1) mythological basis (2) sociological basis, (3) theological basis, and (4) historical basis. The form of implementing the Aci Keburan Tradition at Hyang Api Temple, Kelusa Traditional Village begins with the preparatory stage, the implementation stage and the final stage of carrying out the aci keburan or panyineban tradition. The philosophical values contained in the aci burial tradition are educational values, socio-cultural values, ethical or ethical values, tattwa values and togetherness values.